2017
DOI: 10.1097/mib.0000000000001117
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes After Primary Infliximab Treatment Failure in Inflammatory Bowel Disease

Abstract: Primary infliximab treatment failure is associated with poor outcome including high risk of surgery or sustained active disease despite medical interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Failures to biologicals are well-known hard-to-treat patients, and treatment responses to any biological in this cohort are expected to be low. 3 54 Along with a low sample size, this might explain the rather high rate of non-responders in the present study. In patients showing partial response to vedolizumab induction therapy, a shortened dosing interval of one or several doses was initiated to ensure adequate drug levels, although these were not measured.…”
Section: Discussionmentioning
confidence: 75%
“…Failures to biologicals are well-known hard-to-treat patients, and treatment responses to any biological in this cohort are expected to be low. 3 54 Along with a low sample size, this might explain the rather high rate of non-responders in the present study. In patients showing partial response to vedolizumab induction therapy, a shortened dosing interval of one or several doses was initiated to ensure adequate drug levels, although these were not measured.…”
Section: Discussionmentioning
confidence: 75%
“…PNR after the initiation of TNF-α inhibitors need to be assessed early due to their poor prognosis [7]. However, the response rate can gradually increase from the first to the third administration of TNF-α inhibitors [4, 9].…”
Section: Summary Of the Meetingmentioning
confidence: 99%
“…Thus, in clinical settings, there are partial responders (PR) categorized as neither PNR nor responders, who display a partial response without satisfying effects in the induction phase of TNF-α inhibitors. Primary treatment failure of TNF-α inhibitors can be associated with poor long-term outcomes, including a high risk of surgery or sustained active disease despite medical interventions [7]. Patients who failed to obtain an ideal initial response show poor outcome, while Buhl et al [8] reported that the population with deep remission increased to 25% at 2 years after IFX initiation among patients who had partial response after 1 year of IFX treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, patients with primary failure of IFX often had no response to the second-line biologic drugs, thus leading to prolonged disease activity (Roblin et al, 2018;Roblin et al, 2020). So far, there is no international consensus on how to handle IBD patients with failure of anti-TNF (Allez et al, 2010;Papamichael et al, 2015;Buhl et al, 2017). Appropriately choosing other therapies after anti-TNF failure was a common challenge to clinicians, yet little is known about the prognosis after the failure in the long term (Hanauer et al, 2002;Allez et al, 2010).…”
Section: Introductionmentioning
confidence: 99%